Chronic disease influences over 40 major life‐changing decisions (MLCDs): a qualitative study in dermatology and general medicine. (18th October 2013) - Bhatti, Z.U.; Finlay, A.Y.; Bolton, C.E.; George, L.; Halcox, J.P.; Jones, S.M.; Ketchell, R.I.; Moore, R.H.; Salek, M.S.
Abstract Background Chronic disease not only impairs patients' psycho‐social well‐being but also influences major life‐changing decisions (MLCDs). There is little information about the types of MLCDs affected and the long‐term consequences. Objectives The aims were to identify the MLCDs influenced by chronic disease, to define 'MLCD' and to suggest support strategies for patients taking MLCDs. Methods Adult dermatology patients explained how their chronic disease had influenced MLCDs in individual interviews. Adult patients from other medical specialities gave similar information by postal survey. NVivo8 software was used for qualitative analysis of data. Themes were categorized through a coding–recoding iterative process. Results There were 308 evaluable responses (male 55.2%; mean age = 51.8 years, mean disease duration = 19 years) from the 365 (55.7%) responses to the 655 patient invitations. These were used to generate themes to conceptualize 'MLCDs'. The most frequently reported MLCDs in the dermatology interviews concerned career choice (66%), job (58%), choice of clothing (54%), relationships (52%), education (44%), stopping swimming (34%), moving abroad (32%), not socializing (34%), wearing make‐up (22%) and having children (22%). In the postal survey early retirement (40.6%), impact on job (29.4%), having children (24.8%), career choice (22.4%) and relationships (15.5%) were most commonly reported. The number of MLCDs reported by individuals was inversely related to age. Forty‐one affected MLCD themes were grouped into 18 MLCD categories. A definition of MLCD was developed and strategies suggested to support patients. Conclusions Chronic diseases influence a wide range of MLCDs. MLCDs are a novel domain in disease burden assessment. Clinicians' knowledge about this is important in patient management.